Religious diversity and entrepreneurship in transition: Lessons for policymakers - Elena Nikolova; Dora Simroth (IZA Journal of European Labor Studies, 2015)
Using the 2010 Life in Transition Survey, we show that localities with higher religious diversity have more respondents who have tried to set up a business. Although religious diversity also correlates with a higher start-up probability (following trial), this effect is driven by access to finance and risk preferences. We provide suggestive evidence that the positive association between religious diversity and entrepreneurial trial is positively moderated by social capital (when measured as access to weak ties and the ability to bridge structural holes). Our results suggest that programs which encourage entrepreneurial attempts in diverse areas and develop such social capital are likely to be particularly effective. At the start-up stage, relaxing credit constraints should rank high on the policy agenda.
Keywords: J15; L26; P23; 330; Entrepreneurship; Diversity; Transition region